Integration of the proteome and transcriptome reveals multiple levels of gene regulation in the rice dl2 mutant - Peng, Xiaoyan; Qin, Zhongliang; Zhang, Guopeng; Guo, Yaomin; Huang, Junli (Frontiers in Plant Science, 2015)
Leaf vascular system differentiation and venation pattern plays a key role in transporting nutrients and keeping the plant shape, which is an important agronomic trait for improving photosynthetic efficiency. However, knowledge about the regulation of leaf vascular specification and development is little. Here we utilized the rice midribless mutant (dl2) to investigate the molecular changes in transcriptome and proteome proﬁlings during leaf vascular specification and differentiation. Using isobaric tag for relative and absolute quantiﬁcation (iTRAQ) and digital gene expression (DGE) technique, a nearly complete catalogue of expressed proteins and mRNAs was acquired. From the catalogue, we reliably identified 3172 proteins and 9865230 tags mapped to genes, and subsets of 141 proteins and 98 mRNAs, which were differentially expressed between dl2 mutant and wild type. The correlation analysis between the abundance of differentially expressed mRNA and DEPs (differentially expressed proteins) revealed numerous discordant changes in mRNA/protein pairs and modest correlation was observed, indicative of divergent regulation of transcription and translational processes. The DEPs were analyzed for their involving in biological processes and metabolic pathways. Up- or down-regulation of some key proteins confirmed that the physiological process of vascular differentiation is an active process. These key proteins included regulated proteins that had not previously reported to be associated with vascular differentiation process, and there are alterations in the expression of proteins that are involved in spliceosome pathway. Together, our results show that the developmental and physiological process of leaf vascular system is a thoroughly regulated and complicated process, in which proteins involved might be beneficial for genetically modification to regulate the development of leaf vascular.